Determinants of the Proportion of Tabarru’ Funds Sharia Life Insurance Companies in Indonesia - Tesha Aprilyani (UIN Mataram, 2020)
Financial management of the Sharia Life insurance company uses a system of funds separation (Islamic Split Fund Theory). The fund separation system is to separate the assets and liabilities of the Tabarru Fund group from the Company's Fund group. The government has not set the problem of distribution of Tabarru ' and Ujrah, therefore the Sharia life insurance entity determines the proportion of Tabarru ' and Ujrah in its operations, so that there is a difference in the proportion of distribution of tabarru ' and Among Sharia life insurance companies. The purpose of this research is to test variable determinant proportion of tabarru funds ' on Sharia life insurance. The research methods used in this study are causality methods with a quantitative approach. The population in this research is the Sharia life insurance company registered with the Financial Services Authority (OJK). The purposive sampling method is used for the sample determination of this research. The statistical analysis techniques used in this study were the analysis of the regression data panels. The dependent variables in this study are the proportion of tabarru funds ' and independent variables in the study of the level of claims, retakaful activities, and operating expenses. The results showed that the retakaful activity had an effect on the proportion of the Tabarru ' fund in a positive direction, the operating burden negatively impacted the proportion of the Tabarru ' fund. On the other hand, the claim variable has no influence on the proportion of the Tabarru fund '.